O impacto das políticas direcionadas à primeira infância sobre o índice de mortalidade infantil no Rio Grande do Sul - Guasch, Fabiene Silva Batista Rosa (2022)
Infant mortality is a collective health problem exacerbated by the socioeconomic disparities of a country. The World Health Organization (WHO, 2020) points out that infant mortality rates between 2000 and 2019 had a significant reduction in Brazil, according to the population projection made by the Brazilian Institute of Geography and Statistics (IBGE, 2013). The variation was from 29.02 per thousand live births in 2000 to 13.82 in 2015. This social indicator portrays the reality of families living in a situation of socioeconomic vulnerability and highlights the need for public policies to face the problem. In this context, the Better Early Childhood Program (PIM) and the Happy Child Program (PCF), one at the state level and the other nationwide, aim to promote comprehensive care and care focused on early childhood. These programs have articulated actions in the areas of health, education, social assistance, human rights and culture, with a priority audience: children, pregnant women and families in situations of social vulnerability. Given the above, the study sought to analyze the impact of policies aimed at early childhood (PIM and PCF) on infant mortality in the municipalities of Rio Grande do Sul. Thus, the objectives presented in this work were: to analyze the spatial distribution of the infant mortality rate in the territory of Rio Grande do Sul, comparing its values in the participating and non-participating municipalities in the PIM and the PCF; to correlate the infant mortality rate with health expenditures and the GDP per capita of the municipalities and, finally, to assess whether the intervention of the PIM and PCF public policy contributed to the reduction of the infant mortality rate in Rio Grande do Sul. For this, the Exploratory Analysis of Spatial Data (AEDE) was carried out in order to observe the distribution of this rate in the municipalities. Afterwards, the Differences in Differences (DD) methodology was applied. Regarding the results, the child assistance programs had an estimated impact of -0.266 for the PIM and -0.612 for the PCF, which indicates that public policies are contributing to reduce the mortality rate in the territory of Rio Grande do Sul. Thus, the results of this study can help to identify ways to improve public actions aimed at children in vulnerable families.